Au cœur de la face cachée de la ville : observer, comprendre et penser la nuit - Nicolas Chausson (Bollettino della Società Geografica Italiana, 2019)
Over the past two decades, the urban night has been coveted to promote economic and social opportunities. However, nights are too often analyzed through a prism of conflicts and regulation of conflicts. Subsequently, nights are seldom approached as a true dimension of our cities. However, the urban night provides a wealth of knowledge to those who are interested in the urban fact. Following day time, it actually presents another feature of our cities. Referring to other territories, but also to different activities, economies and populations, or altered practices, the night is a time of temporary readjustment of a complete territorial system. Based on scientific research and illustrating our point through the case study of the nights in Lyon urban area, we propose to review this underside of the city. First of all, we will present the singularities and what is at stake in the urban night. Then, we will propose some essential reflection on how to take care of our nights, between animation and appeasement of the city.